catena-poly[tetramethylammonium[[(nitrato-kappa O-2,O ')dioxouranium]-mu(3)-sulfato]] - Doran, M; Norquist, A; O'Hare, D (2003)
The title compound, {(C4H12N)[UO2(NO 3)(SO4)]}n, contains one-dimensional anionic [UO2(NO3)(SO4)]- chains, with the charge balanced by tetramethylammonium cations. Each U atom is seven-coordinate, in a pentagonal bipyramidal geometry. Each sulfate tetrahedron bridges three adjacent uranium centres and each nitrate anion shares an edge with a [UO 7] polyhedron. © 2003 International Union of Crystallography Printed in Great Britain - all rights reserved.